First record of the desert shrew Notiosorex crawfordi in México City - Márquez-Villalba, Galo Ludwig; Martínez-Coronel, Matías; Rivera-Tellez, Diego; Galeana-Barrera, Luis Enrique; Pérez-Hernández, Raúl Balam (Therya Notes, 2022)
The genus Notiosorex comprises 5 species typical of xeric habitats in northern México, except for N. crawfordi, whose previous southernmost record is located in the state of Hidalgo. This study reports the first record of this species in a more southern locality, México City. The corpse of a shrew specimen was found in the Tecuautzin Volcano and transported to the Universidad Autónoma Metropolitana-Iztapalapa to recover the skin and skeleton. We took 22 measurements of the skull and jaw with the ImageJ 1.8.0 software. The specimen was deposited in the National Collection of Mammals at Universidad Nacional Autónoma de México. The specimen was an adult male of the genus Notiosorex with lateral skin glands in the body, three unicuspid maxillary teeth, and maxillary premolar with partial reddish pigmentation, which are traits typical of the genus. The specimen was identified as N. crawfordi based on the glenoid fossa extending laterally and the free paraoccipital process protruding from the exoccipital. The skull and jaw morphometrics lie within the variation reported for the species by other authors. This record of N. crawfordi expands its distribution range to the south and increases to 81 the number of mammal species recorded in México City. The species is listed as Threatened by the Mexican environmental authority, and the sampling site is affected by anthropogenic activity, which jeopardizes the maintenance of the local population. The relevant authorities are encouraged to consider expanding the area of the Sierra de Santa Catarina natural protected area.